Application of Inventory Information Systems as a Work Practice Management Strategy in Improving Technology Learning in Education Management - Hutagalung, Siti Nurhabibah (Edumaniora : Jurnal Pendidikan dan Humaniora, 2024)
The application of technology in education management often faces challenges in efficient inventory management and technology integration in learning. This research aims to evaluate the effectiveness of inventory information systems as a work practice management strategy in enhancing technology learning in educational management. The research method involved a case study in an educational institution where an inventory information system was implemented. Data were collected through interviews with management staff, observation of work processes, and analysis of the effectiveness of the system through improved operational efficiency and quality of technology learning. The main results showed that the implementation of the inventory information system improved the efficiency of resource management and strengthened technological learning in educational management. In conclusion, the implementation of an inventory information system is recommended as an effective solution to improve the quality of management and learning in education.